Effect of manual physical therapy on sleep quality and jaw mobility in patients with bruxism: A biopsychosocial randomized controlled trial - El-Gendy, Mohamed H.; Ibrahim, Mostafa M.; Helmy, Emad S.; Neamat Allah, Neama H.; Alkhamis, Batool Abdulelah; Koura, Ghada M.; Hamada, Hamada A. (Frontiers in Neurology, 2022)
This study aimed to investigate the effect of deep stripping massage and trigger points pressure release massage on Pittsburg sleep quality index (PSQI), jaw mobility and pressure pain threshold (PPT) of masticatory muscles in patients with sleep bruxism. A randomized controlled trial was conducted among 45 patients diagnosed with sleep bruxism. Patients were randomly assigned to three groups; control group “group I, 5 males and 10 females”, deep stripping massage group “group II, 2 males and 13 females”, and pressure release massage group “group III, 4 males and 11 females”. Patients were tested twice; before and after a six-week period during which group I received transcutaneous electrical nerve stimulation and passive stretch, group II received deep stripping message and group III received trigger points pressure release message. Findings revealed significant improvements in PSQI (p=0.0001), jaw opening (p=0.0001), jaw protrusion (p=0.0001), jaw left lateral movement (p=0.004), jaw retraction (p=0.0001), right temporalis PPT (p=0.0001), left temporalis PPT (p=0.0001), right master PPT (p=0.001), left master PPT (p=0.001), right lateral pterygoid PPT (p=0.001), left lateral pterygoid PPT (p=0.001), right diagstric muscle PPT (p=0.001) and left diagstric muscle PPT (p=0.001) in the post-test condition in group II compared with group I and group III. Deep stripping massage was effective in improving PSQI, jaw mobility and PPT of masticatory muscles compared with trigger points pressure release message and traditional treatment technique in patients with sleep bruxism.